MANAGEMENT STRATEGY DEVELOPMENT OF THE FURUDUL AINIYAH MOVEMENT PROGRAM - Munawwaroh, Izzatul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This reseach the Management Strategy Development of the Furudul Ainiyah MTs Syafiiyah Besuk Program. This research uses a qualitative case study approach, the research subjects consist of the Head of the Madrasah and several Deputy Heads. Data collection techniques use interviews, documentation, observation. Data analysis techniques use data reduction, data presentation, and drawing conclusions. The focus of this research is that the researcher wants to describe the Management Strategy Development of the Furudul Ainiyah MTs Syafiiyah Besuk. This research data was obtained through interviews, observation and documentation. In the next stage, researchers checked the validity of the data by extending participation, diligent observation and triangulation. To get more accurate and reliable results, researchers conducted interviews with the Head of Madrasah, Head of Student Affairs, Head of Curriculum and Teachers at MTs Syafiiyah Besuk. The research results show that strategic management through the Furudul Ainiyah Program has a positive impact on religious education, morality and the character of students at MTs Syafiiyah Besuk. SWOT analysisbased strategy formulation provides a strong basis for understanding internal strengths, identifying external opportunities, and overcoming challenges and weaknesses. The implementation of the strategy shows that innovative teaching methods create an interesting learning environment, encourage student participation, and strengthen understanding of religious values in character formation. Evaluation of key strategies for sustainability and continuous improvement, with evaluation results highlighting successful implementation and identifying areas of potential improvement, such as expanding parent involvement or adapting teachers' teaching methods at MTs Syafiiyah Besuk.